Comparison of anti-thrombotic strategies using Bivalirudin, Heparin plus Eptifibatide, and Unfractionated Heparin Monotherapy for acute coronary syndrome (ACS) patients undergoing percutaneous coronary intervention (PCI): A single-center observational stu (University Heart Journal, 2021)
Objective: To determine and compare the incidence of in-hospital and 30-day hemorrhagic complication and major adverse cardiac events (MACEs) as evidence of safety and efficacy using three different anti- thrombotic strategies using Bivalirudin, Heparin plus Eptifibatide (GPI: GP IIb/IIIa inhibitor), and Unfractionated Heparin (UFH) monotherapy in acute coronary syndrome (ACS) patients undergoing percutaneous coronary intervention (PCI) in a tertiary care cardiac hospital. Background: UFH or Heparin plus Eptifibatide or Bivalirudin is the most commonly used antithrombotic regimen to improve peri and post-PCI clinical outcomes in a patient undergoing PCI for ACS. Among them, the most effective and optimal antithrombotic regimen for preventing ischemic complications while limiting bleeding risk in ACS patients undergoing PCI is still far from being clear. Methods: 324 ACS patients ( age >18 years and ≤75 years) who underwent PCI from May 2018 to May 2019 at UCC, BSMMU, Dhaka were consecutively enrolled in the study and were divided into three groups according to antithrombotic. The choice of Anti-thrombotic strategy was at the discretion of the operator(s) and the patient’s affordability. Group-A: 107 patients received Bivalirudin as intravenous (I/V) bolus of 0.75 mg/ kg, followed by an infusion of 1.75 mg/kg/hr up to 4 hours. Group-B: 111 patients received UFH as an I/ V bolus of 70-100 U/kg (targeted ACT: 250-300 s). Group-C: 106 patients were administered UFH plus Eptifibatide as per the standard hospital guidelines. Dual antiplatelet (DAPT) loading as Aspirin 300 mg plus P2Y12 inhibitors ( Clopidogrel 600 mg or Prasugrel 60 mg or Ticagrelor 180 mg) was given in all patients before the procedure. The maintenance dose of DAPT was continued for at least one month and patients were followed telephonically up to 30 days. The outcome measures were in-hospital and 30-day hemorrhagic complication and MACEs [death, MI, stroke, stent thrombosis and target-vessel revascularization (TVR)] Results: In-hospital outcome: Patients treated with Bivalirudin as compared with UFH had a significantly lower incidence of QMI lesions (0% vs.6%; p=0.038) and major bleeding (0% vs. 7%; p=0.021). The bleeding rate was also significantly lower in Bivalirudin arm as compared with Heparin plus GPI arm (0% vs. 6%; p=0.038). However, the incidence of cardiac death, stent thrombosis, TVR were no differences among the three groups. 30-day outcome: There was only one NQMI in the bivalirudin group as opposed to 8% in the heparin group (p=0.041). No other adverse effects were found significantly different among the study groups. Conclusion: In this perspective, observational study of ACS patients undergoing PCI in a single-center showed that Bivalirudin monotherapy is safer than other contemporary antithrombotic strategies. In terms of efficacy, Bivalirudin is non inferior to Heparin plus Eptifibatde but superior to UFH monotherapy.University Heart Journal Vol. 17, No. 2, Jul 2021; 91-98